Efficacy Study on Training by Using Hydrogel to Improve Swallowing Function in Patients with Dysphagia after Stroke - HUANG Shaochun; XU Jianzhen; LIU Li; RAO Jiang; QIU Haiyan; YU Canping; ZHANG Jie; LI Shujie (康复学报)
ObjectiveTo explore the clinical efficacy on training by using hydrogel to improve swallowing function in patients with dysphagia after stroke.MethodsIn accordance with the diagnostic criteria of stroke established by Neurology Society of Chinese Medical Association, a total of 80 patients with dysphagia after stroke and Functional Oral Intake Scale (FOIS) with FOIS grade 1-3 were enrolled from May 2020 to October 2020. According to the random number table, they were randomly divided into observation group and control group, with 40 cases in each group. In addition to the routine swallowing rehabilitation treatment by the routine nasogastric tube treatment, the observation group was given oral feeding training of hydrogel under nasal feeding state for 3 weeks. Before and after treatment, the swallowing function of the two groups was determined by FOIS, the leakage aspiration was assessed by Penetration-Aspiration scale (PAS), and the efficacy was evaluated by the rate of nasogastric tube removal. The mean FOIS, PAS and the extubation rate of nasogastic tube were compared between the two groups before and after treatment.ResultsThere was statistically significant difference in FOIS grade in the control group before and after treatment (χ2=38.892, P<0.001), while there was no statistically significant difference in PAS grade (χ2=11.987, P>0.05). The extubation rate of nasogastic tube in the control group was 25%. The difference of FOIS and PAS grade in the observation group before and after treatment was statistically significant (χ2=94.517, P<0.001), and the extubation rate of nasogastic tube in the observation group was 100%. There were statistically significant differences between the observation group and the control group before and after treatment in the mean FOIS grade, the composition ratio of PAS grade and the extubation rate (FOIS: χ2=86.176, P<0.001; PAS: χ2=57.411, P<0.001; Extraction rate: χ2=48, P<0.001).ConclusionThe application of hydrogel in oral feeding training can significantly improve the swallowing function of patients with dysphagia after stroke. Combined with standardized feeding process management, the extubation rate can be significantly improved, which is helpful for patients to realize safe oral feeding as soon as possible.